PEMBERDAYAAN MASYARAKAT MELALUI DIVERSIFIKASI LIMBAH KOPI ARABIKA GAYO MENJADI DIFFUSER AROMATERAPI COVID-19 - Sri Setiawaty; Muhammad Muhammad; Reza Putra; Riska Imanda; Nur Octavia Deri; Ratih Permana Sari (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2022)
Coffee is a mainstay commodity in Bener Meriah Regency, Aceh. Coffee beans contain chemicals such as caffeine, chlorogenic acid, trigonelin, carbohydrates, fats, amino acids, organic acids, minerals and volatile aromas that can produce aromatherapy effects. The use of synthetic air freshener has a negative impact on health because the volatile organic compounds released are classified as toxic compounds and carcinogens. Aromatherapy diffusers are a good choice to avoid these risks, apart from being a relaxation, it can also improve air quality, which in turn acts as a COVID-19 preventive effort. Through this Community Service program, the Malikussaleh University PKM teams helps coffee farmer partners to develop an aromatherapy diffuser product from sorted coffee bean waste or rejected/pixel coffee, namely coffee with broken conditions, holes, seeds that are too young and too old. This program is a strategic step in the context of pioneering and building micro-enterprises in Weh Tenang Uken Village so that it can improve the economy of the community and its surroundings.